Photonic Generation of Triangular-Shaped Waveform With Tunable Symmetry Factor Based on Two Single-Drive Mach-Zehnder Modulator - Chuangye Wang; Tigang Ning; Jing Li; Li Pei; Jingjing Zheng; Guobin Ren; Beilei Wu; Xiaowei Dong (IEEE Photonics Journal, 2020)
An approach to generating triangular-shaped waveform with variable symmetry based on two single-drive Mach-Zehnder Modulator is proposed and analyzed. By setting the bias state of modulators, the rotation angle of polarization controller, phase shift of phase shifters and the modulation index of modulators properly, triangular-shaped waveforms with different symmetry can be synthesized in time-domain. The detailed theoretical analysis and simulation are given. Triangular-shaped waveforms with different symmetry factor (0%–100%) are obtained in simulation. Compared with previous scheme for generating triangular-shaped waveforms with different symmetry, the generated triangular-shaped waveform in this paper is more similar to the ideal waveform.